Engineering of the upper hinge region of human IgG1 Fc enhances the binding affinity to FcγIIIa (CD16a) receptor isoform. Issue 6 (9th October 2018) - Ashoor, Dana N; Ben Khalaf, Noureddine; Bourguiba-Hachemi, Sonia; Marzouq, Maryam H; Fathallah, M Dahmani
Abstract: The interaction between antibodies and Immune cells surface FcγRIIIa (CD16a) receptor triggers a variety of immune responses including antibody-dependent cell-mediated cytotoxicity, antibody neutralization, phagocytosis, inflammation and tissue injury. Recent studies showed that IgG1 upper hinge region and FcγRs polymorphism play a major role in the interaction with Fcγ receptors and in the stability of the immune complex hence, in mounting strong inflammatory response. To further investigate this issue, we developed a tool box of IgG1 Fc isoforms to depict the affinity between mutated IgG1 Fc regions and extracellular domain variants (V158F) of CD16a. Our strategy consisted of designing different random upper-hinge mutated variants of IgG1 Fc domain, reproducing the naturally occurring two variants of CD16a and producing all of them as recombinant fusion proteins in Pichia Pastoris . The interactions were assayed using the Surface Plasmon Resonance (Biacore) method along with an in silico analysis to identify the major interaction and key residues that underline the affinity between the Fc region and CD16a variants. Our data showed that the affinity of the Fc region to the CD16a is strongly correlated to polar interactions. This molecular engineering approach yielded an IgG1Fc mutant with enhanced binding affinity to CD16a F158 variant.